ESHRE PGT Consortium data collection XIX–XX: PGT analyses from 2016 to 2017†. Issue 3 (27th July 2021) - van Montfoort, A; Carvalho, F; Coonen, E; Kokkali, G; Moutou, C; Rubio, C; Goossens, V; De Rycke, M
Abstract: STUDY QUESTION: What are the trends and developments in pre-implantation genetic testing (PGT) in 2016–2017 as compared to previous years? SUMMARY ANSWER: The main trends observed in this 19th and 20th data set on PGT are that trophectoderm biopsy has become the main biopsy stage for PGT for aneuploidies (PGT-A) and that the implementation of comprehensive testing technologies is the most advanced with PGT-A. WHAT IS KNOWN ALREADY: Since it was established in 1997, the ESHRE PGT Consortium has been collecting and analysing data from mainly European PGT centres. To date, 18 data sets and an overview of the first 10 years of data collections have been published. STUDY DESIGN, SIZE, DURATION: The data for PGT analyses performed between 1 January 2016 and 31 December 2017 with a 2-year follow-up after analysis were provided by participating centres on a voluntary basis. Data were collected using a new online platform, which is based on genetic analysis as opposed to the former cycle-based format. PARTICIPANTS/MATERIALS, SETTING, METHODS: Data on biopsy method, diagnostic technology and clinical outcome were submitted by 61 centres. Records with analyses for more than one PGT for monogenic/single gene defects (PGT-M) and/or PGT for chromosomal structural rearrangements (PGT-SR) indication or with inconsistent data regarding the PGT modality were excluded. All transfers performed within 2 years after the analysis were included enabling the calculation of cumulative pregnancy rates. Data analysis, calculations, figures and tables were made by expert co-authors. MAIN RESULTS AND THE ROLE OF CHANCE: The current data collection from 2016 to 2017 covers a total of 3098 analyses for PGT-M, 1018 analyses for PGT-SR, 4033 analyses for PGT-A and 654 analyses for concurrent PGT-M/SR with PGT-A. The application of blastocyst biopsy is gradually rising for PGT-M (from 8–12% in 2013–2015 to 19% in 2016–2017), is status quo for PGT-R (from 22–36% in 2013–2015 to 30% in 2016–2017) and has become the preferential biopsy stage for PGT-A (from 23–36% in 2013–2015 to 87% in 2016–2017). For concurrent PGT-M/SR with PGT-A, biopsy was primarily performed at the blastocyst stage (93%). The use of comprehensive diagnostic technology showed a similar trend with a small increased use for PGT-M (from 9–12% in 2013–2015 to 15% in 2016–2017) and a status quo for PGT-SR (from 36–58% in 2013–2015 to 50% in 2016–2017). Comprehensive testing was the main technology for PGT-A (from 66–75% in 2013–2015 to 93% in 2016–2017) and for concurrent PGT-M/SR with PGT-A (93%). LIMITATIONS, REASONS FOR CAUTION: The findings apply to the data submitted by 61 participating centres and do not represent worldwide trends in PGT. Details on the health of babies born were not provided in this manuscript. WIDER IMPLICATIONS OF THE FINDINGS: Being the largest data collection on PGT in Europe/worldwide, the data sets provide a valuable resource for following trends in PGT practice. STUDY FUNDING/COMPETING INTEREST(S): The study has no external funding and all costs are covered by ESHRE. There are no competing interests declared. TRIAL REGISTRATION NUMBER: N/A.